The (Power) Struggle: Experiences of BIWOC Correctional Officers at Rikers Island Jail - Martin-Howard, Simone (Women & criminal justice, 2024)
To understand the experiences of Black, Indigenous, and Women of Color (BIWOC) correctional officers (COs) with justice-involved individuals and other staff, we draw on interviews with 15 BIWOC COs at Rikers Island. Despite power differential between COs and justice-involved individuals, participants described relatability through their shared backgrounds and upbringings. We found that relatability minimized the distance between them and may be particularly beneficial for confined persons of color. Nevertheless, hierarchical power dynamics shaped power struggles between BIWOC COs concerning mutual respect and professionalism in the workplace, coupled with power differentials reinforced by BIWOC supervisors in their decision-making.